(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
Motivation plays a crucial role in the process of language learning, determining how much effort learners put into acquiring a new language and how persistently they engage with the material. This article explores the significance of motivation in second language learning (SLL), examining its various types—intrinsic and extrinsic—and the psychological theories that explain how motivation influences success.